Língua Ticuna: aspectos da variação linguística em Feijoal, Região do Alto Solimões - Gabino (Meyaecü), Josiney Basto (2024)
The main goal of this study is that of identifying features for the investigation of linguistic variation in Feijoal, one of the major Tikuna communities, and one that, unlike most other Tikuna communities, sits on the right bank of the Solimões River. The events related to the foundation of the community are recovered from an oral narrative, and, from this, we arrive at certain conclusions and hypotheses. During the entire process of recording and studying the text, we sought explanations for certain practices and uses of language based on the study of narratives. The Tikuna form the largest indigenous group of the Brazilian Amazon, also having communities in Peru and Colombia. The majority of Tikuna communities is found in Brazil, making up a total surpassing 100 (one hundred) settlements, each with a speech community manifesting linguistic variation within the Tikuna language, which is, moreover, the first language (native languages) of the majority of the members of this ethnic group. Although many of the indigenous communities of the region have been recognized, recorded and included in databases of institutions, it is still the case that the amount of research directed towards the description, analysis and documentation of indigenous languages and, in particular, to variation internal to the Tikuna language, remains very limited. In view of this situation, our work fits within broader efforts to remedy this situation, notably through building a dialogical interaction between Linguistics, the study of indigenous languages, of language variation and basic education.